Processed data from Limited vocal compensation for elevated ambient noise in bearded seals: implications for an industrializing Arctic ocean - Michelle E. H. Fournet (10144626); Margherita Silvestri (10144629); Christopher W. Clark (10144632); Holger Klinck (289713); Aaron N. Rice (10144635) (2021)
Data used for statistical analysis, data summary, and modeling